Talin1 promotes HCC progression by regulating NRG1/PI3K/AKT pathway - Jialong liu; Yao Lu; Bowen Zheng; Deng Huang; Juxian Song; Baolin Wang; Shuguo Zheng (Discover Oncology, 2024)
Abstract Objective of the study Hepatocellular carcinoma (HCC) stands as the third leading cause of cancer-related mortality globally. Metastasis, responsible for treatment failures, underscores the urgency to comprehend molecular drivers of invasion and migration. Central to the invasive and migratory processes underlying metastasis is the protein Talin1. However, the role and underlying mechanisms governing Talin1's involvement in HCC have remained elusive. Methods A total of 100 HCC specimens were collected from patients who underwent hepatectomy in our center. The expression level of talin1 was measured to evaluate the correlationship of talin1 and the development of HCC. In vitro and in vivo experiments were conducted to verify the characteristic of talin1 in HCC. RNA-seq and bioinformatics analysis were performed to identify the downstream signal pathway of talin1 and their impact on HCC development. Results Here, we reported elevated levels of Talin1 mRNA and protein in HCC tissues. Meanwhile, downregulation of Talin1 significantly reduced the HCC cell proliferation and metastasis in vitro and in vivo. Furthermore, elevating NRG-1, a downstream target of Talin1, enhanced metastasis of HCC cells. More importantly, attenuation of Talin1 inhibited HCC progression through decreasing the stabilization of NRG1 mRNA, consequently regulating the expression of NRG1 and its involvement in mediating the PI3K/AKT pathway. Conclusion Taken together, Talin1 regulates cellular proliferation, metastasis, and invasiveness by modulating NRG1/PI3K/AKT axis, suggesting that Talin1 emerges as a promising candidate for treating HCC.